Reingeniería de procesos de la cooperativa de ahorro y crédito gestión para el desarrollo “Coopgestión” de la ciudad de Quito - Yumbillo Lema, José Arturo (2015)
The present research work was focused on performing a reengineering of existing processes in the Cooperativa de Ahorro y CréditoGestiónpara el Desarrollo in its Operational Management and Support, in the Operations Management there are credit processes, finance and operations operationalized with subprocesses. In Credits there are concession, finance, accounting, operations, cashbox and customer services; in Management Support we have security, control and maintenance, which are vital for the development of the organization, being these media and ongoing coordination, this way allows to do registers and transmit in an orderly and systematic the necessary information in this financial organization. Using all methods, technical and technological means are used to support in order to fulfillment of the proposed objectives by investors. The main objective to the literature review is to make know in a theoretically form the different instances covering the process reengineering in the different areas of analysis such as operational management and operative and administrative management to the Cooperativa de Ahorro y CréditoGestiónpara el Desarrollo. In order to fulfill the objectives outlined in developing this work, It was performed many interviews firstly to the Manager and subsequently to employees, thereby allowing to know the reality of organizational structure and the procedures to follow in order to compliance the most important process of the Cooperative. In the process reengineering a new organizational structure is detailed with the new organizational elements proceed to operationalize; describing the activities to each process with their flow diagrams for the application of these instruments efficiently in all services provided by the Cooperative, to satisfy customers who are the reason for being of this financial institution in developing . The conclusions that have been reached are the follows; it does not have a consistent organizational structure according to the operation, there is a partial lack of knowledge about process management, we were able to get the objectives outlined, to make reengineering for operational and administrative processes and put your knowledge. It is recommended that new processes generated in the Operational and Administrative area are executed immediately in order to optimize the activities in the different services provided by the Cooperative "GOOPGESTION" To conclude this summary, we present the bibliography, which detail the research sources such as books, websites and documents provided by the Cooperative, concluding with Annexes